2020
DOI: 10.1097/nmd.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits in Men With Substance Use Disorder

Abstract: There has been no study in the literature evaluating autistic traits (ATs) in men with substance use disorders (SUDs). Therefore, we performed the current study to evaluate whether there is a relation between the ATs among men with SUDs and normal controls. A total of 142 men with SUDs and 109 age and sex-matched healthy controls were included in the current study. Present attention deficit hyperactivity disorder (ADHD) symptoms of the participants were evaluated using the Adult ADHD Self-Report Scale. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Tureck et al (2015) revealed a positive correlation between the severity of autistic symptoms and inattention/impulsivity. It has been reported that autistic traits increase behavioral problems (Saito et al, 2017), substance use disorder (Lundström et al, 2011), and are associated with attention deficit hyperactivity disorder symptoms (Isik et al, 2020). Grant and Chamberlain (2021) determined a correlation between autistic traits and attentional impulsivity in university students who gambled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tureck et al (2015) revealed a positive correlation between the severity of autistic symptoms and inattention/impulsivity. It has been reported that autistic traits increase behavioral problems (Saito et al, 2017), substance use disorder (Lundström et al, 2011), and are associated with attention deficit hyperactivity disorder symptoms (Isik et al, 2020). Grant and Chamberlain (2021) determined a correlation between autistic traits and attentional impulsivity in university students who gambled.…”
Section: Discussionmentioning
confidence: 99%
“…It is a 4-point Likert-type self-report questionnaire consisting of 50 questions and comprises five domains: social skill, attention switching, attention to detail, communication, and imagination (Baron-Cohen et al, 2001). High scores on the scale indicate increased autistic traits (Isik et al, 2020). The validity and reliability of the Turkish version have been evaluated previously (Köse et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation